Quality, Service, and Price: Key Drivers of Food Purchase Decisions in Indonesia: Kualitas, Layanan, dan Harga: Faktor Utama Keputusan Pembelian Makanan di Indonesia - Intan Dewi Oktafiyanti; Supardi; Dewi Komala Sari (Academia Open, 2024)
This study aims to determine the purchase decision on product quality, service quality, and price of Nasi Goreng 69 in Sidoarjo. In this study using quantitative research and this study using a sampling technique that is Non Probability Sampling with Accidental Sampling type. The sample in this research is 96 respondents. Sources of data collection using a questionnaire method that uses a Likert scale 1-5. The data analysis method uses the Partial Least Square (PLS) analysis with the Outer Model and Inner Model Tests. The results of this study indicate that variable product quality effect on purchasing decisions, variable service quality effect on purchasing decisions and variable price effect on purchasing decisions